National Heritages and the Law, A Book Review “Perlindungan Negara atas Warisan Budaya Bangsa”, Dr. Diah Imaningrum Susanti, S.H., M.Hum, M.Pd, Setara Press Malang, 2018, 192 Pages, ISBN: 978-602-6344-53-3 - Helmi, Hanif (JILS (Journal of Indonesian Legal Studies), 2021)
The obligation to appoint a competent authority based on national provisions to provide protection for published works whose authors are not known to represent the interests of the creators and protect the rights of the creators is one of the problems in the context of protecting cultural heritage in the copyright dimension in Indonesia. The book "Perlindungan Negara atas Warisan Budaya Bangsa" contains theoretical and juridical foundations in how the state provides adequate legal instruments in the protection of the nation's cultural heritage in Indonesia.